PANDANGAN MAQASHIDU AL-SYARIAH TERHADAP KINERJA FISKAL DAN TATA KELOLA SISTEM EKONOMI - Kusyanto, Andri (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2019)
One of the dominant factors that influence a country's economic performance is the political economy system used. In the new order era the fiscal policy adopted was with a budget deficit based on the economic system known as the economic system of the Pancasila democracy. Based on previous literature studies, researchers have examined a lot about how the economic system is applied and fiscal policy becomes its supporting instrument. So that the assumption arises whether fiscal performance based on the economic system is applied in accordance with Islamic law. In this article, researchers analyze fiscal performance in Indonesia using the Maqashidu sharia perspective. By using the phenomenology approach, this research explores data from phenomena that occurred during the New Order era which were examined qualitatively by comparing economic and maqashidu syariah theories. The purpose of this research is to find out the fiscal performance and its application in terms of Islamic law using Maqashidu sharia instruments. After conducting research, the authors found that fiscal implementation in Indonesia was based on the Pancasila economic system and used budget deficit policies. Furthermore, the budget deficit policy aims to maintain economic stability in the macro sector, political stability and national security. The goal is mandatory and absolute. The main conclusion is based on the findings of the authors that fiscal policy and its application based on the Pancasila economic system are stated to be permissible Islamic perspective. With god or absolute reason and must be done if it aims to meet the needs or meet many people